The war against the terror masters why it happened, where we are now, how we'll win. - Ledeen, Michael Arthur (St. Martin's Griffin, 2003)
The author explains how and why the United States was so unprepared for the September 11th catastrophe; the nature of the terror network we are fighting -- including the state sponsors of that network; the role of radical Islam; and the enemy collaboration of some of our traditional Middle Eastern "allies"; -- and, what we must do to win the war. The book examines the two sides of the war: the rise of the international terror network, and the past and current efforts of our intelligence services to destroy the terror masters in the U.S. and overseas. It also visits every country in the Near East and describes the terrorist cancers in each. Among many the many topics are: how the terror network survived the loss of its main sponsor, the Soviet Union; how the FBI learned from a KGB defector of the existence of Arab terrorist sleeper networks inside the United States; how moralistic guidelines straight-jacketed the FBI from even collecting a file of newspaper clippings on known terror groups operating in America; how the internal culture of the CIA, and severe limitations on its ability to operate, blinded us to the growth of terror networks; and much more.